(untitled) (Revista Internacional de Formação de Professores, 2024)
During their professional careers, teachers construct and re-signify their teaching knowledge, and moments of continuing education are especially conducive to such mobilization. This study aims to identify how the elaboration of reflective narratives and their collective discussion bring elements of the construction and restructuring of teaching knowledge by teachers participating in a training course on Critical Environmental Education and Media Literacy. To this end, we developed a qualitative study that analyzed 27 reflective narratives and the discussion established by the teachers during a conversation circle after writing the reports. It was possible to perceive that the teachers were able to reflect and re-evaluate their own practices, became aware that they were still professionals in training, and established relationships between personal knowledge, school knowledge, and teaching experience. We also showed that, by exchanging experiences, successes, and difficulties, new knowledge was constructed by the teachers and much of the knowledge already acquired was re-signified.